Computational Purposing Phytochemicals against Cysteine Protease of Monkeypox Virus: An In-silico Approach - Poonam Bansal; Mahiti Gupta; Sonali Sangwan; Gurpreet Kaur Bhatia; Seema Ramniwas; Deepak Chandran; Abhijit Dey; Kuldeep Dhama; Hardeep Singh Tuli (Journal of Pure and Applied Microbiology, 2022)
The development and evolution of viruses that cause disease have presented a formidable challenge to contemporary medicine and the global economy, not to mention a catastrophic risk to human health. Almost all of these viruses are zoonotic, meaning they were first identified in animals and then spread to humans. An emerging virus may cause only a few isolated instances, resulting in a limited outbreak, or it may cause widespread infection and spread to other parts of the world, triggering a full-blown epidemic. These kinds of emerging occurrences have occurred frequently and in many different forms during the past few decades. Monkeypox is a zoonotic disease caused by the monkeypox virus, a member of the orthopox family that also includes variola, cowpox, and vaccinia. Both animals and humans can get infected by this virus. Similar to smallpox this disease shows less severe rashes and lower mortality rate. The outbreak of monkeypox was declared a global public health emergency by the World Health Organization in July 2022. Unknown mutations and variations are linked to the recent epidemic. Presently, FDA approved tecovirimat, cidofovir and brincidofovir are there in market to treat monkeypox virus. But there are some side effects of these drugs as they are synthetic. So, scientists are working on natural remedies that can be used as alternative to these drugs. In the present study virtual screening of phytochemicals (N-(2-Allylcarbamoyl-4-chloro-phenyl)-3,4-dimethoxy-benzamide, 6-Dimethylaminonaphthene-1-sulfonicacid amide, Oleic Acid and dipentyl ester) from Allophylus serratus were employed against core viral cysteine proteases from monkeypox virus was done. The docking study revealed that selected ligands bind with target viral protein with binding affinity in the range of -5.0 to -6.7 kcal/mol. N-(2-Allylcarbamoyl-4-chloro-phenyl)-3,4-dimethoxy-benzamide showed the highest binding affinity of -6.7 kcal/mol which can be investigated in the future to design potential drugs against monkeypox virus. Thus, this study foresees the possibility of bioactive phytochemicals functioning as template molecules for further experimental evaluation of their efficiency against monkeypox virus.